Metodologiczne problemy wyceny wartości sieci gospodarczych opierających się na wiedzy - Perechuda, Kazimierz; Kowalewski, Marcin (The Methodological Problems of the Value Estimation of Net Companies, 2009)
In the paper, the following issues are presented: the dynamics of network companies, the value migration, the knowledge approach in the value creation, the influence of the main components of the net companies to their value.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 329-336